Appropriateness of Prostate Cancer Imaging among Veterans in a Delivery System without Incentives for Overutilization. (30th September 2015) - Makarov, Danil V.; Hu, Elaine Y. C.; Walter, Dawn; Braithwaite, R. Scott; Sherman, Scott; Gold, Heather T.; Zhou, Xiao‐Hua Andrew; Gross, Cary P.; Zeliadt, Steven B.
Abstract : Objective: To determine the frequency of appropriate and inappropriate prostate cancer imaging in an integrated health care system. Data Sources/Study Setting: Veterans Health Administration Central Cancer Registry linked to VA electronic medical records and Medicare claims (2004–2008). Study Design: We performed a retrospective cohort study of VA patients diagnosed with prostate cancer ( N  = 45, 084). Imaging (CT, MRI, bone scan, PET) use was assessed among patients with low‐risk disease, for whom guidelines recommend against advanced imaging, and among high‐risk patients for whom guidelines recommend it. Principal Findings: We found high rates of inappropriate imaging among men with low‐risk prostate cancer (41 percent) and suboptimal rates of appropriate imaging among men with high‐risk disease (70 percent). Veterans utilizing Medicare‐reimbursed care had higher rates of inappropriate imaging [OR: 1.09 (1.03–1.16)] but not higher rates of appropriate imaging. Veterans treated in middle [OR: 0.51 (0.47–0.56)] and higher [OR: 0.50 (0.46–0.55)] volume medical centers were less likely to undergo inappropriate imaging without compromising appropriate imaging. Conclusions: Our results highlight the overutilization of imaging, even in an integrated health care system without financial incentives encouraging provision of health care services. Paradoxically, imaging remains underutilized among high‐risk patients who could potentially benefit from it most.